2012
DOI: 10.1016/j.jacc.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Statins, Risk of Diabetes, and Implications on Outcomes in the General Population

Abstract: Risk of diabetes was increased after statins, but outcomes were favorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 34 publications
7
63
0
4
Order By: Relevance
“…It is conceivable that the increased risk of NOD may be specific to those patients already at high risk of developing diabetes. Fewer data are available on the incidence of NOD in Japanese statin users, but a recent study in a Taiwanese population suggested a similarly small risk of NOD offset by the CV benefits of statin therapy 136) , as has been reported previously in predominantly Western populations.…”
Section: Conflicts Of Interestmentioning
confidence: 67%
“…It is conceivable that the increased risk of NOD may be specific to those patients already at high risk of developing diabetes. Fewer data are available on the incidence of NOD in Japanese statin users, but a recent study in a Taiwanese population suggested a similarly small risk of NOD offset by the CV benefits of statin therapy 136) , as has been reported previously in predominantly Western populations.…”
Section: Conflicts Of Interestmentioning
confidence: 67%
“…Based on registry or prescription-based data, previous studies have reported that statin treatment was associated with higher risk of type 2 DM onset ranging from 10-46% (12,30,31). In a collaborative meta-analysis of 13 randomised statin trials including in total nearly 90000 participants, statin therapy was associated with a 9% increased risk for type 2 diabetes, based on fasting plasma glucose concentration values or physician reported diagnosis of diabetes (32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the NCEP ATP Ⅲ guideline, the use of the healthcare reimbursement policy issued by the Taiwan NHI program was associated with less likelihood of LDL-C goal attain- may have a higher LDL-C level, which led their physicians to start or continue statin therapy. Despite that the guidelines used by the physicians were not associated with the statin therapy allocation, the prevalent prescription of the low to medium equipotency doses under the Taiwan NHI program might still be responsible for the low LDL-C control rate observed in our study 7,32) . To improve hypercholesterolemia management in Taiwan, efforts from the healthcare reimbursement system in addition to inputs from both the patients and physicians are necessary.…”
Section: Discussionmentioning
confidence: 64%